1, 3, 4‐Thiadiazole and 1, 2, 4‐triazole‐5‐thione derivatives bearing 2‐pentyl‐5‐phenyl‐2, 4‐dihydro‐3H‐1, 2, 4‐triazole‐3‐one ring: Synthesis, molecular docking, urease inhibition, and crystal structure. Issue 1 (31st October 2022) - Gültekin, Ergün; Bekircan, Olcay; Kara, Yakup; Güler, Halil İbrahim; Soylu, Mustafa Serkan; Kolaylı, Sevgi
Abstract: Two series of 1, 3, 4‐thiadiazole (40a–o ) and 1, 2, 4‐triazole‐5‐thione (41a–l ) derivatives bearing a 2‐pentyl‐5‐phenyl‐1, 2, 4‐triazole‐3‐one ring were synthesized and then studied for their urease inhibitory activities using thiourea as a standard drug. Among the two groups, the first group (40a–o ) did not show good activity while the second group (41a–l ) showed excellent activity. Compound 41j (1091.24 ± 14.02 µM) of the second series of compounds showed lower activity than thiourea, while the remaining 11 compounds (41a–i, k, and l ) showed better activity than thiourea (183.92 ± 13.14 µM). Among the 11 compounds, 41b (15.96 ± 2.28 µM) having the 3‐F group on the phenyl ring showed the highest inhibitory activity. Urease kinetic studies of 41b, which is the most active compound, determined it to have an un‐competitive inhibition potential. Moreover, in silico analysis against urease from jack bean with 27 new heterocyclic compounds and the reference molecule was carried out to see the necessary interactions responsible for urease activity. The docking calculations of all compounds supported stronger binding to the receptor than the reference molecule, with high inhibition constants. In addition, compound 40m was characterized by single‐crystal X‐ray diffraction analysis. X‐ray analysis reveals that the structures of the compound 40m crystallize in the monoclinic P21/c space group with the cell parameters: a  = 10.2155(9) Å, b  = 22.1709(18) Å, c  = 21.4858(17) Å, β  = 99.677(8)°, V  = 4797.0(7) Å 3 . X‐ray diffraction analyses were also performed to gain insights into the role of weak intermolecular interactions and C‐H…X (halogen) interactions in compound 40m that influence the crystal packing. Abstract : Two series of 1, 3, 4‐thiadiazole (40a–o ) and 1, 2, 4‐triazole‐5‐thione (41a–l ) derivatives bearing a 2‐pentyl‐5‐phenyl‐1, 2, 4‐triazole‐3‐one ring were synthesized and studied for their urease inhibitory activities, with the second group showing excellent activity. The most active compound (41b ) is shown to be an uncompetitive inhibitor. Docking calculations of all compounds supported stronger binding to the receptor than the reference molecule.